2009
DOI: 10.1177/1066896909332113
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Likelihood of Additional Nodal Metastases in Breast Carcinoma Patients With Positive Sentinel Node Biopsy

Abstract: Axillary lymph node dissection (ALND) is an important procedure in the staging of breast cancer patients. However, it is associated with a significant morbidity rate. In addition, using early diagnosis a high number of cases with negative lymph nodes can be identified. A lymph node defined as sentinel lymph node (SLN) would be the first to receive tumoral drainage. A less morbid but accurate staining procedure using mapping and SLN biopsy has been introduced. The aim of this study was to estimate the likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…By monovariate analysis of the factors that influenced axillary nodal status, our data confirm a linear correlation between tumor size and the number of metastatic nodes [27]. The patient's age proved to have a controversial role among SLNB indicators, and it should not be an absolute exclusion criterion for this procedure.…”
Section: Discussionsupporting
confidence: 70%
“…By monovariate analysis of the factors that influenced axillary nodal status, our data confirm a linear correlation between tumor size and the number of metastatic nodes [27]. The patient's age proved to have a controversial role among SLNB indicators, and it should not be an absolute exclusion criterion for this procedure.…”
Section: Discussionsupporting
confidence: 70%
“…Age, menopausal status, HT, HG, size of the tumour, lymphatic and blood vessel invasion, and hormone receptor status are previously studied factors. Despite the inhomogeneity of data concerning predictors of axillary positivity, the literature review and our results pointed to tumour size and lymphovascular invasion as factors having an influence on axillary metastatic rates (9,(15)(16)(17)(18)(19). Recently, in a prospective study of 177 patients concerning early invasive breast cancer treatment via tumour excision and SLNB, TS (p=0.003) and LVI (p=0.01) appeared to be the only histopathological characteristics having a significant association with lymph node positivity in multivariate analysis (36).…”
Section: Resultsmentioning
confidence: 64%
“…However, the Cambridge model and a novel Turkish formula seem to be uninfluenced by SLN micrometastasis and non-SLN positivity Table 6. Analysis of the impact of lymphovascular invasion on sentinel lymph node metastasis (literature review) (9,(15)(16)(17)(18)(19) rates and have an area under the ROC curve of over 80% each, and thus deserve further validation in prospective trials (13,14,35). Age, menopausal status, HT, HG, size of the tumour, lymphatic and blood vessel invasion, and hormone receptor status are previously studied factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerb-2 is a well known negative prognostic factor in breast cancer; however, our knowledge about its effect on lymph node metastasis is limited. Only in 1 article by Mustac et al [25] Cerb-2 status was found to correlate with the overall status of the axilla (pN). In addition, the authors of the models that were used in our study did not state whether they tested Cerb-2 as a variable in their models.…”
Section: Nomogram Resultsmentioning
confidence: 99%